Climate change and the potential effects on maternal and pregnancy outcomes: an assessment of the most vulnerable – the mother, fetus, and newborn child - Charlotta Rylander; Jon Øyvind Odland; Torkjel Manning Sandanger (Taylor & Francis Group, 2013)
In 2007, the Intergovernmental Panel on Climate Change (IPCC) presented a large amount of evidence about global warming and the impact of human activities on global climate change. The Lancet Commission have identified a number of ways in which climate change can influence human health: lack of food and safe drinking water, poor sanitation, population migration, changing disease patterns and morbidity, more frequent extreme weather events, and lack of shelter. Pregnant women, the developing fetus, and young children are considered the most vulnerable members of our species and are already marginalized in many countries. Therefore, they may have increased sensitivity to the effects of climate change. Published literature in the fields of climate change, human health, tropical diseases, and direct heat exposure were assessed through the regular search engines. This article demonstrates that climate change will increase the risk of infant and maternal mortality, birth complications, and poorer reproductive health, especially in tropical, developing countries. Thus, climate change will have a substantial impact on the health and survival of the next generation among already challenged populations. There is limited knowledge regarding which regions will be most heavily affected. Research efforts are therefore required to identify the most vulnerable populations, fill knowledge gaps, and coordinate efforts to reduce negative health consequences. The effects of malnutrition, infectious diseases, environmental problems, and direct heat exposure on maternal health outcomes will lead to severe health risks for mothers and children. Increased focus on antenatal care is recommended to prevent worsening maternal health and perinatal mortality and morbidity. Interventions to reduce the negative health impacts caused by climate change are also crucial. Every effort should be made to develop and maintain good antenatal care during extreme life conditions as a result of climate change.